Employee-Manager Alliances and Shareholder Returns from Acquisitions - Masulis, Ronald W.; Wang, Cong; Xie, Fei (Journal of Financial and Quantitative Analysis, 2020)
We examine the potential for management-worker alliances when employees have substantial voting rights, and how such alliances affect the balance of power between managers and shareholders. We find that substantial employee voting rights exacerbate the manager-shareholder conflicts. Specifically, they entrench incumbent managers and allow them to pursue value-destroying acquisitions by undercutting the disciplinary influence of the corporate control market. Importantly, employee support for managers is conditional on favorable treatment of employees. Our findings are consistent with Pagano and Volpin’s theory of worker-management alliances and highlight the potential risks associated with large employee voting power.